K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: \(\Leftrightarrow x^2-2x+1+y^2+4y+4=0\)

=>(x-1)^2+(y+2)^2=0

=>x=1 và y=-2

b: \(\Leftrightarrow2x^2+2y^2-16x+32+16y+32=0\)

\(\Leftrightarrow2\left(y-4\right)^2+2\left(x+4\right)^2=0\)

=>y=4; x=-4

17 tháng 9 2018

a) \(x^2\left(y-z\right)+y^2\left(z-x\right)+z^2\left(x-y\right)\)

\(=x^2\left(y-z\right)-y^2\left[\left(y-z\right)+\left(x-y\right)\right]+z^2\left(x-y\right)\)

\(=x^2\left(y-z\right)-y^2\left(y-z\right)-y^2\left(x-y\right)+z^2\left(x-y\right)\)

\(=\left(y-z\right)\left(x^2-y^2\right)-\left(x-y\right)\left(y^2-z^2\right)\)

\(=\left(y-z\right)\left(x-y\right)\left(x+y\right)-\left(x-y\right)\left(y-z\right)\left(y+z\right)\)

\(=\left(x-y\right)\left(y-z\right)\left(x+y-y-z\right)\)

\(=\left(x-y\right)\left(y-z\right)\left(x-z\right)\)

17 tháng 9 2018

c) \(\left(x+y+z\right)^3-x^3-y^3-z^3\)

\(=\left[\left(x+y\right)+z\right]^3-x^3-y^3-z^3\)

\(=\left(x+y\right)^3+z^3+3z\left(x+y\right)\left(x+y+z\right)-x^3-y^3-z^3\)

\(=\left[\left(x+y\right)^3-x^3-y^3\right]+3z\left(x+y\right)\left(x+y+z\right)\)

\(=3xy\left(x+y\right)+3\left(x+y\right)\left(xz+yz+z^2\right)\)

\(=3\left(x+y\right)\left(xy+xz+yz+z^2\right)\)

\(=3\left(x+y\right)\left[x\left(y+z\right)+z\left(y+z\right)\right]\)

\(=3\left(x+y\right)\left(y+z\right)\left(x+z\right)\)

d) \(\left(x^2+y^2-5\right)^2-4x^2y^2-16xy-16\)

\(=\left(x^2+y^2-5\right)^2-\left(4x^2y^2+16xy+16\right)\)

\(=\left(x^2+y^2-5\right)^2-\left[\left(2xy\right)^2+2.2xy.4+16\right]\)

\(=\left(x^2+y^2-5\right)^2-\left(2xy+4\right)^2\)

\(=\left(x^2+y^2-5-2xy-4\right)\left(x^2+y^2-5+2xy+4\right)\)

\(=\left(x^2-2xy+y^2-9\right)\left(x^2+2xy+y^2-1\right)\)

\(=\left[\left(x-y\right)^2-3^2\right]\left[\left(x+y\right)^2-1\right]\)

\(=\left(x-y-3\right)\left(x-y+3\right)\left(x+y-1\right)\left(x+y+1\right)\)

e) \(\left(x^2+4y^2-5\right)^2-16\left(x^2y^2+2xy+1\right)\)

\(=\left(x^2+4y^2-5\right)^2-4^2\left(xy+1\right)^2\)

\(=\left(x^2+4y^2-5\right)^2-\left[4\left(xy+1\right)\right]^2\)

\(=\left(x^2+4y^2-5\right)-\left(4xy+4\right)^2\)

\(=\left(x^2+4y^2-5-4xy-4\right)\left(x^2+4y^2-5+4xy+4\right)\)

\(=\left(x^2+4y^2-4xy-9\right)\left(x^2+4y^2+4xy-1\right)\)

\(=\left[\left(x-2y\right)^2-3^2\right]\left[\left(x+2y\right)^2-1\right]\)

\(=\left(x-2y-3\right)\left(x-2y+3\right)\left(x+2y-1\right)\left(x+2y+1\right)\)

f) \(\left(x-y+5\right)^2-2\left(x-y+5\right)+1\)

\(=\left(x-y+5-1\right)^2\)

\(=\left(x-y+4\right)^2\)

26 tháng 11 2017

a) \(x^2-xy+x-y\)

\(=\left(x^2-xy\right)+\left(x-y\right)\)

\(=x\left(x-y\right)+\left(x-y\right)\)

\(=\left(x+1\right)\left(x-1\right)\)

b) \(2xy-x^2-y^2+16\)

\(=16-\left(x^2-2xy+y^2\right)\)

\(=4^2-\left(x-y\right)^2\)

\(=\left(4-x+y\right)\left(4+x-y\right)\)

c) \(x^2-6x-16\)

\(=x^2-6x+9-25\)

\(=\left(x^2-6x+9\right)-25\)

\(=\left(x-3\right)^2-5^2\)

\(=\left(x-3-5\right)\left(x-3+5\right)\)

\(=\left(x-8\right)\left(x+2\right)\)

26 tháng 11 2017

a)  x2 - xy + x - y = x(x - y) + (x - y) = (x - y)(x + 1)

b) 2xy - x2 - y2 + 16 = 16 - (x - y) = (4 - x + y)(4 + x - y)

c) x2 - 6x - 16 = (x - 3)2 - 25 = (x - 3 - 5)(x - 3 + 5) = (x - 8)(x + 2)

8 tháng 9 2016

DÀI THẾ AI LÀM NỔI

21 tháng 8 2018

a ) \(x^2\left(x+3\right)+y^2\left(y+5\right)-\left(x+y\right)\left(x^2-xy+y^2\right)=0\)

\(\Leftrightarrow x^3+3x^2+y^3+5y^2-\left(x^3+y^3\right)=0\)

\(\Leftrightarrow3x^2+5y^2=0\)

Do \(\left\{{}\begin{matrix}3x^2\ge0\forall x\\5y^2\ge0\forall y\end{matrix}\right.\)

\(\Rightarrow3x^2+5y^2\ge0\forall x;y\)

Dấu " = " xảy ra

\(\Leftrightarrow\left\{{}\begin{matrix}3x^2=0\\5y^2=0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}x^2=0\\y^2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\y=0\end{matrix}\right.\)

Vậy \(x=0;y=0\)

b )\(\left(2x-y\right)\left(4x^2+2xy+y^2\right)+\left(2x+y\right)\left(4x^2-2xy+y^2\right)\)

\(-16\left(x^3-y\right)=32\)

\(\Leftrightarrow\left[\left(2x\right)^3-y^3\right]+\left[\left(2x\right)^3+y^3\right]-16x^3+16y=32\)

\(\Leftrightarrow8x^3-y^3+8x^3+y^3-16x^3+16y=32\)

\(\Leftrightarrow16y=32\)

\(\Leftrightarrow y=2\)

Vậy \(y=2\)

haha